Cambridge pimary English : (Cambridge University Press, 2015)
This Teacher's Book includes the following features. A complete mapping grid to the Cambridge Primary English curriculum framework. Step-by-step teaching notes including opportunities for differentiated learning and spelling link boxes to highlight where spelling practice could be integrated. Fully cross-referenced for the most effective use of the Cambridge Primary English Learner's Book and Activity Book. Over 30 Photocopy masters (PCMs) and photocopiable spelling lists. A CD-ROM including PDFs of the Teacher's Book content for printing and reference.